2017
DOI: 10.1111/1751-2980.12436
|View full text |Cite
|
Sign up to set email alerts
|

Factor analysis of recurrent biliary events in long‐term follow up of gallstone pancreatitis

Abstract: In the long-term follow up of GSP, cholecystectomy can offer better protection against recurrent biliary events than EST only. The presence of CBD stones at time of definitive therapy might be a risk factor for recurrent biliary events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 16 publications
(40 reference statements)
0
6
1
Order By: Relevance
“…Even so, three out of four patients who developed biliary complications during follow-up did not have choledocholithiasis after the index episode of pancreatitis, and only 11 % of the forthcoming biliary complications were due to remaining bile duct stones. Even though the presence of bile duct stones during the index pancreatitis event has been considered an independent risk factor for recurrence (21), we did not find statistically significant differences. However, despite the fact that almost 90 % of our patients were studied for biliary tract occupation, only 70 % underwent a standard imaging test with MRCP, echoendoscopy, or ECRP.…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…Even so, three out of four patients who developed biliary complications during follow-up did not have choledocholithiasis after the index episode of pancreatitis, and only 11 % of the forthcoming biliary complications were due to remaining bile duct stones. Even though the presence of bile duct stones during the index pancreatitis event has been considered an independent risk factor for recurrence (21), we did not find statistically significant differences. However, despite the fact that almost 90 % of our patients were studied for biliary tract occupation, only 70 % underwent a standard imaging test with MRCP, echoendoscopy, or ECRP.…”
Section: Discussioncontrasting
confidence: 88%
“…However, the combination of both eliminates the risk entirely, suggesting the possibility of retained lithiasis that was not discovered on imaging tests (21,22).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, it was notable that almost half of the patients did not undergo cholecystectomy either before or after ERCP, which may be attributed to their advanced age and associated comorbidities. 17 Surprisingly, we found that having undergone cholecystectomy (either before or after ERCP) increased the risk of developing long-term benign complications. These findings contrast with what has been reported in other studies, 18 where post-ERCP cholecystectomy is associated with an overall decrease in biliopancreatic complications following ERCP.…”
Section: Discussionmentioning
confidence: 72%
“…Unlike the majority of studies evaluating the occurrence and risk of RBE and complications in delayed cholecystectomy [ 7 , 13 , 17 , 19 , 21 , 24 , 28 , 35 ], the present study rather examined the outcome in patients suffering RBE independently of the timing of surgery. Even if the occurrence of surgical complications did not reach statistical significance between groups, open cholecystectomy, either planned or converted, was significantly more frequent in patients who had RBE (Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…ERCP remains insufficient, since recurrence of CBDS occurs in up to 30% [ 4 , 14 ], and recurrence of any related biliary events (RBE) in up to 47% of the cases [ 15 , 16 ] despite clearance of the common bile duct (CBD). While ERCP fails to prevent further RBE [ 7 , 16 – 18 ], cholecystectomy does prevent the RBE in majority of the cases [ 15 , 17 , 19 , 20 ].…”
mentioning
confidence: 99%